Pemimpin Ideal dan Karakteristik yang Didambakan dalam Menjawab Tantangan Zaman - Christianto Dedy Setyawan; Sariyatun Sariyatun; Cicilia Dyah Sulistyaningrum Indrawati (Universitas Sebelas Maret, 2022)
The existence of a leader is related to the aspects of role models, protection, and decision making. Leaders stand at the forefront of creating the realization of community welfare. The public's initial perception of the figure who is believed to be an ideal leader is often broken by the pattern of policies taken after the election of the figure as a leader. This also applies at the village to provincial levels of government. This social portrait is quite risky because it saves a latent danger in the form of people's disappointment with the leader. Writing this article aims to (1) describe the ideal leader figure coveted by the community and (2) explain the importance of leadership aspects that are able to answer the challenges of the times.This writing is done in descriptive analytical with literature study. The results were obtained: (1) There are aspects that are missed consistently in the community, such as integrity, fairness, and responsibility. The characteristics of positive leaders are able to create public optimism in looking at the future. (2) Leadership based on the foundation of virtuous character is needed in dealing with the dynamics of a rapidly changing era.